Changing employment relations under a fractured corporate elite. (15th March 2019) - Benton, Richard; Hafeez, Aibak; Mun, Eunmi
Abstract: Shareholder power is often cited as contributing to the deterioration of employment relations. However, managerial power also shapes how shareholder pressures affect workers. In this article, we examine how managerial power contributed to the initial durability and eventual decline of white-collar benefits in the era of shareholder primacy. One traditional source of elite power is the network of overlapping board appointments which helped corporate leaders resist shareholder pressures that weaken employment relations and benefits. More recently, this network has begun to fracture and leaders are no longer able to draw on collective resources in resisting shareholders. We investigate how shifting bases of elite power affect white-collar benefits, focusing on employee stock ownership plans, work–life balance policies and profit-sharing plans. Using a panel of S&P 1500 firms from 1998 to 2011, we show that firms densely connected in the board interlock network were more likely to adopt white-collar benefits; but these benefits began to erode as the network fractured. We discuss the consequences of a disempowered corporate elite for employment stability.